Handbook of biomedical telemetry - Nikita, Konstantina S.; Institute of Electrical and Electronics Engineers (Hoboken, New Jersey : John Wiley & Sons Inc., 2014)
"Handbook of Biomedical Telemetry describes the main components of a typical biomedical telemetry system as well as its technical challenges. Author K. S. Nikita addresses technologies for biomedical sensing and design of biomedical telemetry devices with special emphasis on powering/integration issues and materials for biomedical telemetry applications. Covering biomedical telemetry devices, biosensor network topologies and standards, clinical applications, wearable and implantable devices, and the effects on the mobile healthcare system, this compendium is a must have for professional engineers as well as researchers and graduate students"--Provided by publisher.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Biotelemetry; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biotelemetry; Telemetry; Biosensing Techniques; Electronic books; Electronic books